Association between blood cholesterol and sodium intake in hypertensive women with excess weight. Issue 15 (April 2018) - Padilha, Bruna Merten; Ferreira, Raphaela Costa; Bueno, Nassib Bezerra; Tassitano, Rafael Miranda; Holanda, Lidiana de Souza; Vasconcelos, Sandra Mary Lima; Cabral, Poliana Coelho
Abstract : Abstract: Restricted sodium intake has been recommended for more than 1 century for the treatment of hypertension. However, restriction seems to increase blood cholesterol. In women with excess weight, blood cholesterol may increase even more because of insulin resistance and the high lipolytic activity of adipose tissue. The aim of this study was to assess the association between blood cholesterol and sodium intake in hypertensive women with and without excess weight. This was a cross-sectional study with hypertensive and nondiabetic women aged 20 to 59 years, recruited at the primary healthcare units of Maceio, Alagoas, Brazilian Northeast. Excess weight was defined as body mass index (BMI) ≥25.0 kg/m 2 . Sodium intake was estimated by the 24-hour urinary excretion of sodium. Blood cholesterol was the primary outcome investigated by this study, and its relationship with sodium intake and other variables was assessed by Pearson correlation and multivariate linear regression using a significance level of 5%. This study included 165 hypertensive women. Of these, 135 (81.8%) were with excess weight. The mean sodium intake was 3.7 g (±1.9) and 3.4 g (±2.4) in hypertensive women with and without excess weight, respectively. The multiple normal linear regression models fitted to the "blood cholesterol" in the 2 groups reveal that for the group of hypertensive women without excess weight only 1 independent variable "age" is statistically significant to explain the variability of the blood cholesterol levels. However, for the group of hypertensive women with excess weight, 2 independent variables, age and sodium intake, can statistically explain variations of the blood cholesterol levels. Blood cholesterol is statistically inversely related to sodium intake for hypertensive women with excess weight, but it is not statistically related to sodium intake for hypertensive women without excess weight.